Re-engaging with Survey Non-respondents: The BHPS, SOEP and HILDA Survey Experience - Nicole Watson; Mark Wooden (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Previous research into the correlates and determinants of non-response in longitudinal surveys has focused exclusively on why it is that respondents at one survey wave choose not to participate at future waves. This is very understandable if non-response is always an absorbing state, but in many longitudinal surveys, and certainly most household panels, this is not the case. Indeed, in these surveys it is normal practice to attempt to make contact with many non-respondents at the next wave. This study differs from previous research by examining the process of re-engagement with previous wave non-respondents. Drawing on data from three national household panels it is found that the re-engagement decision is indeed distinctly different from the decision about continued participation. Further, these differences have clear implications for the way panel surveys should be administered given the desire to enhance overall response rates.
Keywords: 330; Household panel surveys; survey response; attrition; Befragung; Statistische Methode; Panel; Australien; Deutschland; Großbritannien